2015
DOI: 10.1115/1.4029453
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Single- and Dual-Media Thermocline Tanks for Thermal Energy Storage in Concentrating Solar Power Plants

Abstract: A molten-salt thermocline tank is a low-cost option for thermal energy storage (TES) in concentrating solar power (CSP) plants. Typical dual-media thermocline (DMT) tanks contain molten salt and a filler material that provides sensible heat capacity at reduced cost. However, conventional quartzite rock filler introduces the potential for thermomechanical failure by successive thermal ratcheting of the tank wall under cyclical operation. To avoid this potential mode of failure, the tank may be operated as a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Solid-state packed-bed storage media experience a high degree of temperature stratification due to the large density difference of hot and cold fluid and can form a thermocline region between hot and cold regions which is susceptible to mixing. The thermocline region needs to be minimized to maximize high temperature storage. , …”
Section: Low-cost Thermal Energy Storagementioning
confidence: 99%
“…Solid-state packed-bed storage media experience a high degree of temperature stratification due to the large density difference of hot and cold fluid and can form a thermocline region between hot and cold regions which is susceptible to mixing. The thermocline region needs to be minimized to maximize high temperature storage. , …”
Section: Low-cost Thermal Energy Storagementioning
confidence: 99%
“…The discharge efficiency of the thermocline tank was found to increase with the increasing 𝑅𝑅𝑅𝑅 , opposite to the trend under adiabatic condition. Mira-Hernández et al [32] reported that the heat loss under non-adiabatic condition could cause inhomogeneous internal flow for the whole tank due to the cooling of molten salt near the tank wall. But the total heat lost during charge/discharge the cycle was estimated to be negligible compared to the heat storage capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Air worked as HTF and no liquid option was contemplated. Another concept removes all the solid filler material, obtaining a single-media thermocline tank with fluid only [10]. Even though convective mixing flows are significant without the porous media, the thermal diffusivity lessens, so it can achieve a slightly better thermal function.…”
Section: Introductionmentioning
confidence: 99%